Infrared-to-visible frequency upconversion in transparent glass ceramics containing trivalent-rare-earth-doped nanocrystals - Gouveia-Neto, Artur S.; Da Costa, Ernande B.; Bueno, Luciano A. [UNESP]; Ribeiro, Sidney J.L. [UNESP] (SPIE, the international society for optics and photonics, 2004)
In this work we report on visible upconversion emission in Er 3+-, and Ho3+-doped PbGeO3-PbF 2-CdF2-based transparent glass ceramics under 980 nm infrared excitation. In erbium-doped vitroceramic samples, blue(410 ran), green(530, and 550 nm) and red(660 nm) emission signals were generated, which were identified as due to the 2H9/2, 2H 11/2, 4S3/2, and 4F9/2 transitions to the 4I15/2 ground-state, respectively. Intense red(650 nm) upconversion emission corresponding to the 5F5 - 5I8 transition and very small blue(490 nm) and green(540 nm) signals assigned to the 5F 2,3 - 5I8 and 4S2, 5F4 - 5I8 transitions, respectively, were observed in the holmium-doped samples. The 540 nm is the dominant upconversion signal in Ho3+-doped vitroceramics under 850 nm excitation. The dependence of the upconversion processes upon pump power and doping concentration are also investigated, and the main routes for the upconversion excitation processes are also identified. The comparison of the upconversion process in transparent glass ceramics and the precursor glass was also examined and the results revealed that the former present higher upconversion efficiencies.
Keywords: Glass; Glass-ceramics; Luminescence; Rare-earth; Upconversion; Vitroceramics; Doping (additives); Frequencies; Ground state; Lasers; Nanostructured materials; Rare earth compounds; Solid state device structures; Glass ceramics